Penerapan Metode Quota Based Pada Sistem Informasi Monitoring Pendistribusian Bantuan Sapi Berbasis Website - Saputra, Rizki Adhi; Darusalam, Ucuk (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Cattle is one of the most livestock products in Indonesia, therefore to increase the yield of Indonesian livestock, the government has created a cattle assistance program that can help local breeders in improving the quality and commodities, especially cows, the priority of the program is local cattle to be able to compete. with other imported cattle. With this program, an application is made that can help realize the program. The application that is made is the Information System for Monitoring the Distribution of Cattle Aid where this application is devoted to monitoring all aspects related to distribution. The Information System for Monitoring the Distribution of Cattle Aid can support government programs according to the specified target. Because this government program is aid, this application will be able to accumulate distribution results so that it can be evenly distributed according to the data of prospective recipients that have been set and algorithms that help in running it. This application is a first fit algorithm that can assist in inputting and determining memory locations that can be used to accommodate and minimize fragmentation. The Cattle Assistance Distribution Monitoring Information System assists users in checking data efficiently in terms of timeliness and data accuracy. This study aims to understand the flow and use of information systems in the monitoring and distribution section, the method used to design and create an Information System application for Monitoring the Distribution of Cattle Aid is by observation and document study. The application of this information system monitoring the distribution of cattle assistance has had a good impact on the development of livestock, coupled withsophistication technological and assisted farmers in increasing input and development of livestock in the distribution sector.